HAKIKAT PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM : TUJUAN, MATERI, METODE, DAN EVALUASI - Maulida Salsabila (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Abstract The purpose of this study is to examine how curriculum development in Islamic education takes place. After these objectives are formulated, the task formulation is found. What is the nature of curriculum development in Islamic education? What are the components in the Islamic education curriculum? We also use other sources of information. The findings of this study indicate that the essence of the Islamic education curriculum is a planned effort so that students know, interpret, and practice Islamic teachings as a whole and are able to embed them in the learning process. it is a serious endeavor. The development of an educational curriculum requires the main foundation for formulating objectives and curriculum materials. The foundation includes the foundation of religion, philosophy, psychology and social.